2013
DOI: 10.21149/spm.v55s3.5145
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for the treatment of obesity among children and adolescents in Latin America: a systematic review

Abstract: Objective. The objective of this systematic literature review was to identify evidence-based strategies associated with effective healthcare interventions for prevention or treatment of childhood obesity in Latin America. Materials and methods. A systematic review of peer-reviewed, obesityrelated interventions implemented in the healthcare setting was conducted. Inclusion criteria included: implementation in Latin America, aimed at overweight or obese children and evaluation of at least one obesity-related out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
9
0
1
Order By: Relevance
“…While promising, there are few weight gain prevention interventions specifically focusing on Hispanics/Latinos in the US and Latin America ( 304 , 308 , 327 ). Reviews of childhood obesity interventions in Latin America and the Caribbean report encouraging trends in childhood obesity prevention and treatment programs in schools ( 328 ), healthcare ( 329 ), and settings such as home, summer camps and family clinics ( 330 ). However, these studies were mostly carried out in Mexico and Brazil, only three were randomized clinical trials (RCTs), and most did not include appropriate pediatric measures for BMI or participants’ ages ( 327 ).…”
Section: Interventions To Prevent Type 2 Dm Among Hispanics/latinosmentioning
confidence: 99%
“…While promising, there are few weight gain prevention interventions specifically focusing on Hispanics/Latinos in the US and Latin America ( 304 , 308 , 327 ). Reviews of childhood obesity interventions in Latin America and the Caribbean report encouraging trends in childhood obesity prevention and treatment programs in schools ( 328 ), healthcare ( 329 ), and settings such as home, summer camps and family clinics ( 330 ). However, these studies were mostly carried out in Mexico and Brazil, only three were randomized clinical trials (RCTs), and most did not include appropriate pediatric measures for BMI or participants’ ages ( 327 ).…”
Section: Interventions To Prevent Type 2 Dm Among Hispanics/latinosmentioning
confidence: 99%
“…Previous studies analyzed the effect of physical activity interventions versus interventions that combine physical activity plus diet on BMI, showing a higher effect in the physical activity plus diet interventions groups [27,28]. In Latin America, four previous systematic reviews on interventions aimed at increasing physical activity in children have been performed, some of which were combined with diet intervention [29][30][31][32]. These systematic reviews showed that when physical activity interventions are combined with a nutritional component, they are more effective in producing favourable changes in adiposity (i.e., body parameters, body composition, and BMI).…”
Section: Introductionmentioning
confidence: 99%
“…The rise in overweight and obesity suggests a role for both market and regulatory reforms, and improvements in public understanding. Review evidence highlights the potential to use both health clinics (Nagle et al, 2013) and schools (Verstraeten et al, 2012) to promote healthy eating and exercise. One review argued that in schools multicomponent interventions (for example, promoting healthy eating and exercise through the curricula) were likely to be most effective, and highlighted how involving parents could improve effectiveness (Verstraeten et al, 2012).…”
Section: Programming For Adolescent Health and Wellbeingmentioning
confidence: 99%
“…One review argued that in schools multicomponent interventions (for example, promoting healthy eating and exercise through the curricula) were likely to be most effective, and highlighted how involving parents could improve effectiveness (Verstraeten et al, 2012). As with interventions to reduce undernutrition, it was also noted that the success of particular platforms is dependent on populations having good access to key services (Nagle et al, 2013).…”
Section: Programming For Adolescent Health and Wellbeingmentioning
confidence: 99%